Discovery of ketene/acetyl as a potential receptor for hydrogen-transfer reactions in zeolites - Zhichao Guo; Qingteng Chen; Jian Liu; Bo Yang (Nature Communications)
Abstract Hydrogen-transfer is the primary process responsible for elevating the degree of unsaturation of intermediates in zeolite-catalyzed methanol-to-hydrocarbon reactions, with olefins serving as the typical receptor and alkanes being produced as the by-product. Intriguingly, the introduction of CO was shown to suppress the selectivity of alkanes and enhance the production of aromatics, yet microscopic understanding of this phenomenon remains elusive. Here, based on ab initio molecular dynamics simulations and free energy sampling methods, we discover a non-olefin-induced hydrogen-transfer reaction in the presence of CO, with ketene/acetyl emerging as a more suitable hydrogen-transfer receptor than olefins. This predominant route enhances the degree of unsaturation of olefins without generating additional alkanes, and the produced dienes and acetaldehyde could further contribute to the formation of aromatics. Moreover, we construct a general mechanism applicable to a series of CO-coupled aromatics synthesis reactions, offering distinctive insights and strategies for the optimization of efficiency.